Please Call Again: Correcting Nonresponse Bias in Treatment Effect Models - Behaghel, Luc; Crépon, Bruno; Gurgand, Marc; Le Barbanchon, Thomas (The Review of Economics and Statistics, 2015)
We propose a novel selectivity correction procedure to deal with survey attrition in treatment effect models, at the crossroads of the Heckit model and the bounding approach of Lee (2009). As a substitute for the instrument needed in sample selectivity correction models, we use information on the number of prior calls made to each individual before obtaining a response to the survey. We obtain sharp bounds to the average treatment effect on the common support of responding individuals. Because the number of prior calls brings information, we can obtain tighter bounds than in other nonparametric methods.